MOTIVASI INDONESIA MEMBENTUK INDONESIA TRADE PROMOTION CENTRE (ITPC) DENGAN NIGERIA TAHUN 2010 - Prasetia, Andera; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes the Government of Indonesia policy to create a Indonesia Trade Promotion Center (ITPC) to Nigeria in 2010. Nigeria are one of most country in Africa Continent that have economic potency and from 2000 has been a mitra of Indonesia in economic relationship. In 2004 Nigeria have a implementation policy of economic protection. Ani this policy have influence to export from Indonesia to Nigeria.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze Government of Indonesia policy to create a Indonesia Trade Promotion Center (ITPC) to Nigeria. The theories applied in this research are economic consequences from Friedrich List and national interest concept from Donald. E. Nuchterlain and protecsionisme.The research shows that Government of Indonesia policy to create a Indonesia Trade Promotion Center (ITPC) to Nigeria are because the implementation policy of Nigeria to protect the import from the other countries likes Indonesia and this policy are contra bained policy. In order because the increase of economic scale in Nigeria and be market brief for Indonesia bussiness.Key words: policy, economy, trade, promotion.